Investigating the Relationship Between Mother Tongue Education and Creativity: A Systematic Review at the K-12 Level - Özge Sakaryalı; Mazhar Bal; Yakup Yıldırım (SAGE Open)
Effective use of one’s mother tongue has a positive impact on an individual’s life, especially in mother tongue education at the K-12 level. During this period, students progressively learn to use the language more effectively, which is critical for fostering creativity. Therefore, emphasizing creativity in mother tongue education at the K-12 level is a crucial area. The present study aimed to systematically analyze articles that address creativity in mother tongue education at the K-12 level. Data for the study were collected by searching the Web of Science, Scopus, Ebsco, and the Education Resources Information Center (ERIC) databases based on specific criteria. The analysis included 18 articles. The study’s findings indicate that the examined studies were conducted using different methods and for different purposes. The methodological quality of the studies was evaluated, and it was determined that the average score for qualitative studies was lower than that of quantitative studies. Multiple data collection tools were used in most of the studies. The examined articles consisted of eight themes: writing skills, speaking skills, teaching methods, art, poetry, interculturalism, technology, and reading skills. The findings related to these themes emphasize the complexity of supporting students’ creativity and developing their language skills. The studies lacked significant focus on teaching processes and student-centered approaches, which could provide valuable guidance for future research.